The Columbia River Treaty Renegotiation from the Perspective of Contract Theory. (July 2015) - Brady, Michael; Li, Tongzhe; Yoder, Jonathan
Abstract This paper contributes to the literature on transboundary water agreements by analyzing the Columbia River Treaty renegotiation from the perspective of contract theory. Contract theory has become a powerful part of the economics toolbox but it is much less well known outside of the discipline than game theory. We demonstrate the importance of the concept of contract completeness in identifying efficient contractual arrangements that can consider the tradeoffs of increased flexibility. The limited objectives of the first treaty meant that it was possible to write a complete contract. Climate change and more complex stakeholder interests have moved any future agreement into the realm of incomplete contracts. Alternative types of incomplete contracts are considered as potential future treaty arrangements. The approach used in this study should provide a more general framework for working through potential treaty designs from an efficiency standpoint.